Students’ Outlook on Materials of English for Economics - Susanti, Yeni (Sean Institute, 2025)
In 5.0 industry era, English proficiency is prioritized to satisfy people’s goal in life aspects such as politics, education, business, social and culture. English is taught as a compulsory subject in formal education starting from primary school. For university level, English is taught with varied purposes, depending on their study program to support the basic major or discipline. To fulfill this need, the material should be designed in such a way. When authentic material is offered based on students’ need, actually we are preparing them to meet the demands of the workplace. This study focuses to represent students’ outlook of English material in English for Specific Purpose. A survey took third-semester university student in one of state university in Lampung Province. The result ensures that students show a positive outlook on materials of English for Economics. In terms of material attraction, practicality, authenticity, variety, difficulty level, proportion of language skill and discussed topics, the materials are designed well. However, some additional parts need to be added proportionally